Influence of perceived social support on detection of social norm violation: evidence from N1 and N400 - Liang, Bing; Li, Bingbing; Fan, Xiaoyue; Mu, Yan; Wang, Juan (Frontiers in Psychology, 2024)
The perceived social support individuals receive from their peers plays a crucial role in shaping conformity with social norms. However, the specific mechanism underlying between perceived social support and the detection of social norms remains unclear. This study adopted event-related potentials (ERPs) to investigate this effect by dividing the perceived social support level (low, high) through the Perceived Social Support Scale, and manipulating the type of social norm (conformity, violation) using the social norm violation paradigm. ERP results demonstrated that, compared to the conformity condition, individuals with a lower level of perceived social support elicited greater amplitudes of the N1 component, associated with primary processing, and the N400 component, associated with cognitive conflict, when detecting others' social norm violation. However, no significant differences were appeared in individuals with a high level of perceived social support. The results indicate that, when the perceived social support level of individual is low, detecting others' social norm violation elicits deeper primary processing and stronger cognitive conflict compared to conformity condition.